Pendidikan untuk Kemandirian: Analisis Pemikiran Al-Ghazali dalam Membangun Karakter Siswa - Igo Fadhli Sa’bani; Urai Setiawarni; Siti Fatimah; Herlini Puspika Sari (Reflection : Islamic Education Journal, 2024)
This research examines Al-Ghazali's thoughts in shaping the character of student independence through an educational approach. As one of the important figures in the world of Islamic education, besides concentrating on academics, Al-Ghazali proposed an educational approach that emphasizes the development of strong character. Finding out how Al-Ghazali's education helps students become independent is the driving force for this research as well as its application to the current educational context. The research method is a literature review by analyzing Al-Ghazali's relevant works, such as Ihya Ulumuddin and Mizan al-'Amal. The findings show that there are four main components of education as proposed by Al-Ghazali: moral development, inculcation of religious values, learning life skills, and individual independence. These findings are relevant to the challenges of modern education, especially in the effort to form independent and moral students. Educators can look to the results of this study as a resource in designing a curriculum that facilitates students' self-reliance in a holistic manner.